2022
DOI: 10.3389/fcvm.2022.960531
|View full text |Cite
|
Sign up to set email alerts
|

Variables associated with pulmonary hypertension screened by echocardiography in chronic myeloid leukemia patients on dasatinib therapy

Abstract: BackgroundPulmonary hypertension (PH) is a rare but life-threatening adverse event (AE) of dasatinib, but the associated variables are not clear. This study aimed to explore the variables associated with PH by echocardiography in patients with chronic myeloid leukemia in the chronic phase (CML-CP) receiving dasatinib therapy.MethodsEchocardiography was performed to estimate the probability of PH and pulmonary artery systolic pressure (PASP). Binary logistic analysis and Fine–Gray hazard model were used to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A retrospective study of 451 CML patients on dasatinib who underwent transthoracic echocardiography (TTE) found that 56 (12%) of patients had an elevated right ventricular systolic pressure (RVSP) of 40 mmHg [ 55 ]. In another of study of 243 patients treated with dasatinib, 12.3% had RVSP 40 mmHg after a median follow-up of 27 months [ 58 ]. The results of this study showed an association between pericardial effusion, cardiopulmonary comorbidities, and dasatinib as 3rd line agent (vs 1st line) were associated with PH [ 58 ].…”
Section: Tyrosine Kinase Inhibitors and Pulmonary Arterial Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study of 451 CML patients on dasatinib who underwent transthoracic echocardiography (TTE) found that 56 (12%) of patients had an elevated right ventricular systolic pressure (RVSP) of 40 mmHg [ 55 ]. In another of study of 243 patients treated with dasatinib, 12.3% had RVSP 40 mmHg after a median follow-up of 27 months [ 58 ]. The results of this study showed an association between pericardial effusion, cardiopulmonary comorbidities, and dasatinib as 3rd line agent (vs 1st line) were associated with PH [ 58 ].…”
Section: Tyrosine Kinase Inhibitors and Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…In another of study of 243 patients treated with dasatinib, 12.3% had RVSP 40 mmHg after a median follow-up of 27 months [ 58 ]. The results of this study showed an association between pericardial effusion, cardiopulmonary comorbidities, and dasatinib as 3rd line agent (vs 1st line) were associated with PH [ 58 ]. Dasatinib-induced PAH is typically a chronic process, with a median delay from drug initiation to diagnosis of 34 months [ 54 ].…”
Section: Tyrosine Kinase Inhibitors and Pulmonary Arterial Hypertensionmentioning
confidence: 99%